Structure and similarity of urban forests in the Metropolitan area of Rio de Janeiro - Aquino Santana, Cláudio Alexandre de; Freitas, Welington Kiffer de; Magalhães, Luís Mauro Sampaio (Interciência, 2015)
Tropical forests have different trends of succession, combining natural and anthropogenic factors. In order to identify patterns, data from studies in the Metropolitan Region of Rio de Janeiro, Brasil, between 1993 and 2006 in eight secondary forest remnants were compiled. The method of fixed area plots was used, with tree inclusion criteria of circumference at breast height >15cm. The results show high structural and floristic dissimilarity even in remnants with equal succession time, indicating the existence of multiple pathways for succession in these places. Richness and diversity are directly related to the time of succession, while other attributes vary according to previous land use and features of the site. © 2015, Interciencia Association. All rights reserved.
Estrutura e similaridade em florestas urbanas na Região Metropolitana do Rio de Janeiro